Förekomst av Campylobacter spp. hos kyckling i Sverige 2012–2016 - Schildmeijer, Charlotte (2018)
Sweden experienced a substantial increase in the incidence of human campylobacteriosis during 2016. The aim of this descriptive study was to map out the occurrence and variation of Campylobacter spp. in Swedish broilers for 2012-2016. Data was collected and compiled from the Swedish monitoring program for Campylobacter spp. in broilers. In total, 16 473 samples were analyzed from as many slaughter groups. One sample consisted of pooled contents from ten caeca from ten individual broilers and all samples were collected at the abattoirs. The compilation comprises about 108 producers and six abattoirs in Sweden. The results showed a steady rise in the proportion of slaughter groups positive for Campylobacter spp. from 9% in 2012 to 15% in 2016. A seasonal variation was noticeable with the highest proportion of positive groups during the summer season. Over the study period, one abattoir delivered 60% of the total number of slaughter groups positive for Campylobacter spp., this abattoir slaughtered 52% of the total number of broilers. The total amount sampled and positive slaughter groups varied between the abattoirs during the study period. The percentage of producers who delivered slaughter groups positive for Campylobacter spp. increased from 4667%. During the study period eight producers delivered campylobacter free slaughter groups, proving that this can in fact be done. This report may prove beneficial as a base for other more comprehensive studies regarding the increase of Campylobacter spp. in Sweden’s broilers recorded during the past years.